KEPASTIAN HUKUM PUTUSAN PEMIDANAAN YANG TIDAK BERDASARKAN SURAT DAKWAAN JAKSA PENUNTUT UMUM (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2022)
In criminal law enforcement, there is a problem with the judge made law which is unfair and irresponsible in deciding a case, thereby reducing public trust in the judiciary. Criminal judges in Indonesia make many legal breakthroughs in passing a criminal case decision that does not refer to the provisions of the legislation, in other words the judge carries out his own interpretation of a criminal act that is appropriate for the defendant based on the facts in the trial and sets his own article that fits with the facts of the trial that are seen, resulting in a decision that is not in accordance with the indictment of the public prosecutor. It can be seen that there has been a legal event where the judge has decided outside the prosecutor's indictment and this research needs to be followed up by linking the judge's decision that was handed down not based on the article indicted from the aspect of legal certainty. The type of research used in this research is doctrinal law research. The sentencing decision in a criminal case which is decided by a judge not based on the indictment of the Public Prosecutor can be considered invalid because it is contrary to the principles of criminal law. In the examination in court, the party who must prove the indictment to the defendant is the public prosecutor, not the judge. Keywords: Legal Certainty, Judge made law, Letter Demands, Public Prosecutor